IMPLEMENTASI QANUN ACEH NOMOR 9 TAHUN 2008 TENTANG PEMBINAAN KEHIDUPAN ADAT DAN ADAT ISTIADAT DI GAMPONG LAMIE KECAMATAN DARUL MAKMUR KABUPATEN NAGAN RAYA - Chandra Darussman; Muhammad Ikhwan Adabi; Apri Rotin Djusfi; Phoenna Ath Thariq; Jalaluddin Jalaluddin; Eza Aulia; Fiandy Mauliansyah (Universitas Teuku Umar, 2021)
The enactment of Law Number 11 of 2006 concerning the Government of Aceh has provided a legal basis for Aceh Province to revitalize traditional life in Aceh Province. As an inseparable part of the Aceh Province, Gampong Lamie, Darul Makmur District, Nagan Raya Regency is certainly part of the legal area of the Aceh Qanun No. 9/2008. The implementation of community service activities is carried out by the method of delivering materials directly by displaying materials in the form of Aceh Qanun No. 9 of 2008. Customs settlement of cases in Aceh is recognized by several regional regulations and policies. Article 13 paragraphs (2) and (3) of Aceh Qanun Number 9 of 2008 state that the settlement of 18 types of disputes/disputes between customs and traditions as referred to above is resolved in stages and law enforcement officers provide an opportunity for disputes/disputes to be resolved first. traditionally in the gampong (village) or other names. In addition, it is also stated in the Joint Decree of the Governor of Aceh, the Head of the Aceh Regional Police, and the Chair of the Aceh Customary Council Number: 189/677/2011, 1054/MAA/XII/2011, B/121/I/2012 concerning the Implementation of Gampong and Mukim Customary Courts. Other Names in Aceh.